The design and development of augmented reality filter for promoting speaking fluency teaching in public secondary schools - Nor Sanak, Mohd Nabil (2025)
Speaking fluency is essential in English Language Teaching (ELT), yet teachers face challenges such as limited fluency-focused teaching materials, which is reflected in students’ speaking fluency. Although Augmented Reality (AR) offers immersive educational experience, its use especially markerless AR for supporting speaking fluency teaching remains under explored. Most existing studies on AR focus on vocabulary, revealing a gap and the need to design an AR filter to support fluency teaching in public secondary schools. This study aims to design and develop an Augmented Reality (AR) filter to support speaking fluency teaching in public secondary schools. Design and Development Research (DDR) approach is employed in three main phases: need analysis, design and development, and evaluation. In the first phase, a case study with six participants identified teaching needs. The second phase used the Fuzzy Delphi Method with 11 experts to validate AR filter elements. In the final phase, six participants took part in semi-structured interviews for evaluation. Three key themes emerged in phase one: varied teachers’ definitions of speaking fluency, common fluency teaching activities, and a lack of suitable teaching materials highlighting the need for an Augmented Reality (AR) filter. This determined the need to develop the AR filter for speaking fluency teaching in phase two, expert consensus validated 21 of 22 proposed elements which indicated that only one out of 22 elements proposed was rejected. Phase three revealed that the AR filter supports fluency teaching by offering immersive experiences, enabling personalized instruction, integrating flexibility into lessons, providing simultaneous structured support and fostering fluency development strategies. The integration of validated elements into the AR filter enhances ESL speaking fluency teaching. This study offers practical value by enabling educators to diversify their teaching methods and contributes theoretically by advancing understanding of AR in fluency instruction.